Applications of analysis of variance in wool marketing - Du Plessis, Jasper Johan Jacques (Department of Statistical Sciences, 2023)
Analysis of variance could be described as a statistical technique for analysing measurements depending on several kinds of effects operating simultaneously so as to decide which kinds of effects are important and to estimate the effects. Although probably not susceptible of a very precise definition, it in general consists of a body of tests of hypotheses and methods of estimation using statistics which are linear combinations of sums of squares of linear functions of the observed values. Having been developed mainly in connection with problems of agricultural experimentation, the application thereof in the South African Wool Trade seems non existent. I hope that this thesis will illustrate some of the very useful applications, especially to the extent where the rejection of all (or some) of the hypotheses under consideration is in itself as significant as the acceptance thereof would have been.